The effects of acute normovolaemic haemodilution on peri‐operative coagulation in total hip arthroplasty1. (29th September 2014) - Shin, H. J.; Na, H. S.; Do, S. H.
Summary Total hip arthroplasty results in substantial blood loss in the peri‐operative period. We evaluated the effects of acute normovolaemic haemodilution on blood coagulation and platelet function in 11 patients undergoing total hip arthroplasty. We performed acute normovolaemic haemodilution and haematological tests, rotational thromboelastometry (ROTEM®) and whole‐blood impedance aggregometry. Blood samples were obtained at three time points: (i) before the initiation of acute normovolaemic haemodilution; (ii) 20 min after completion of acute normovolaemic haemodilution; and (iii) 20 min after retransfusion. After acute normovolaemic haemodilution, ROTEM parameters demonstrated hypocoagulability. Clot formation time of INTEM was increased by 31.6% (p = 0.016), whereas the α‐angle and maximum clot formation of INTEM decreased by 8.1% (p = 0.032) and 3.0% (p = 0.013) respectively, compared with baseline values. Clotting time and clot formation time of EXTEM were increased by 40.8% (p = 0.042) and 31.3% (p = 0.016), respectively, whereas the α‐angle and maximum clot formation of EXTEM were decreased by 11.9% (p = 0.020) and 9.5% (p = 0.013), respectively. The maximum clot formation of FIBTEM decreased by 35.1% compared with the baseline value (p = 0.007). Following retransfusion, ROTEM values returned to baseline; clot formation time decreased and the α‐angle and maximum clot formation increased. There were no significant changes in platelet aggregation during the study. At 20 min after the end of acute normovolaemic haemodilution, the international normalised ratio of prothrombin time was increased compared with the baseline value (p = 0.003). We conclude that acute normovolaemic haemodilution resulted in a hypocoagulable state compared with baseline values and that coagulation parameters returned to normal after retransfusion.